Translation, cultural adaptation, validation and reliability of Persian version of Edmonton frailty score questionnaire among Iranian heart failure individuals - Hojatollah Alaei; Mehrbod Vakhshoori; Maryam Heidarpour; Farbod Khanizadeh; Niloofar Bondariyan; Sayed Ali Emami; Davood Shafie; Awat Feizi (Babol University of Medical Sciences, 2023)
Background: Frailty is a common problem in elderly individuals. However, this issue is not well investigated among heart failure (HF) patients with appropriate scales. We aimed to translate and evaluate Edmonton frailty scale (EFS) validity and reliability in Iranian HF adults. Methods: We implemented this methodological study on stable HF patients referred to an outpatient heart clinic in Isfahan, Iran. The translation was done using the forward-backward method. Ten individuals were asked to comment about all items in terms of understandability and simplicity. Fifteen experts were invited, and their ratings on each item were collected to measure the content validity index (CVI) and content validity ratio (CVR). Cronbach's alpha was used for the assessment of internal consistency. After completing the scale for the second time with a two-week interval, test-retest reliability with intraclass correlation coefficient (ICC) measurement was done. Results: The translation process was performed uneventfully. All items were reported to be simple and meaningful. CVI of items ranged from the minimum of 0.80 to a maximum of 1.00 plus an acceptable CVR of at least 0.60. Fifty HF patients (age: 67.2±14.1 years, males: 56%) completed the questionnaire twice without missing data. Cronbach's alpha was first to be 0.550. After omitting three items about social support, drug usage, and nutrition, the value was raised to 0.711. Test-retest reliability showed a good index of consistency (ICC: 0.693, 95% confidence interval: 0.527-0.810). Conclusion: Modified Persian EFS is a simple and meaningful tool with high validity and acceptable reliability for assessing frailty in HF individuals irrespective of age.